L’ETUDE DE L'APPROCHE EXPERIMENTALE DU RESSAUT HYDRAULIQUE DANS UN CANAL RECTANGULAIRE DE FORME COMPOSEE AVEC LIT MAJEUR RUGUEUX - زيد, البشير; أبو العلاء, سلاطنة; عبد الرؤوف, بلال (University of El-Oued, 2022)
"This present memory is intended for the experimental analysis of the hydraulic jump controlled by threshold with thin-walls evolving in a rectangular channel of compound section with a rough major bed. The study made it possible to show the effect of this roughness on the characteristics of the hydraulic jump. it has been possible to obtain purely empirical dimensionless relations that allow us to determine the dimensions of the dissipation basin. " "تهدف هذه المذكرة إلى التحليل، التجريبي الهيدروليكي للقفزة المائية المراقبة بعتبة رقيقة الجدران تتطور في قناة مستطيلة من قسم مركب ذات قاع أعلى خشن. تبحث الدراسة عن تأثير هذه الخشونة على خصائص القفزة. من خلال التحليل التجريبي، المدعوم بالبيانات التجريبية، سمح بالحصول على علاقة تجريبية بحته دون أبعاد التي تمكننا من تحديد أبعاد حوض التبديد لنموذج القفزة الهيدروليكية. "
مذكرات ماستر تخصص ري
Keywords: Keywords: Hydraulic jump, compound rectangular channel, bottom roughness, dissipation basin.; الكلمات الرئيسية: القفز الهيدروليكية، القناة المستطيلة المركبة، خشونة القاع الأعلى، حوض التبديد.